Treatment of Keloid Scars with Botulinum Toxin Type A versus Triamcinolone in an Athymic Nude Mouse Model. Issue 3 (March 2019) - Fanous, Amanda; Bezdjian, Aren; Caglar, Derin; Mlynarek, Aleksander; Fanous, Nabil; Lenhart, Stephanie Fay; Daniel, Sam J.
Abstract : Background: Keloid scarring is a serious condition that mostly affects patients of African or Asian descent. Often disfiguring, this condition can have devastating psychosocial consequences. To date, no treatment modality has been proven ideal. The authors' objectives were (1) to determine the efficacy of botulin toxin type A injection for the treatment of keloid scars compared to steroid injection and to control saline injection (this was achieved through a basic science animal model using athymic nude mice and implanted human keloid tissue); and (2) to analyze the histopathologic changes that occur in an organized keloid scar following botulinum toxin type A injection as compared to steroid and saline injections. Methods: Keloid scars from four patients were excised and implanted subcutaneously into 28 mice. Three small keloid tissue samples were implanted in each of the 28 mice. One week after implantation, each implant received one of three injections: botulinum toxin type A (treatment drug), saline (control), or steroid injection (first-line gold standard). The keloid tissue was extracted 3 weeks after implantation. Weight analysis, immunohistochemistry, and standard hematoxylin and eosin pathologic analysis were performed on each extracted tissue sample. Results: Paired t test analysis of pretreatment and posttreatment tissue weights revealed a statistically significant difference between the treatment and control groups ( p < 0.05). Analysis by a blinded pathologist confirmed fewer collagen bundles in the treatment group. Immunohistochemistry with Ki-67, a marker of cell proliferation, revealed significantly less staining in the treatment groups. Conclusion: Botulinum toxin type A could be an effective treatment for keloid scars.